CRISPR-Cas9 fusion to dominant-negative 53BP1 enhances HDR and inhibits NHEJ specifically at Cas9 target sites - Rajeswari Jayavaradhan (Nature Portfolio, 2019)
Global inhibition of NHEJ factors has been one strategy to improve CRISPR-Cas9 mediated HDR. Here the authors fuse a dominant-negative mutant of 53BP1 to Cas9 to enhance HDR frequency, reduce NHEJ specifically at the Cas9 cut sites, and reduce the toxicity associated with global NHEJ inhibition.